A Study on Brand Preference and Brand Switching Behaviour of Bt Cotton Farmers in Andhra Pradesh - Velavan, C.; Naveen Kumar, S.; Varadha Raj, S. (Indian Journal of Marketing, 2015)
After the introduction of transgenic cotton, Bt cotton gained popularity amongst the farmers in Andhra Pradesh. It created interest among the seed companies to release more transgenic cotton varieties in the country. To reduce the difference between prices of Hybrid and Bt cotton varieties, the Government of Andhra Pradesh forced the seed companies to reduce the prices to curb monopolistic practices. Price reduction motivated the farmers to adopt Bt cotton, which led to the introduction of more varieties from the companies’ side. This study was carried out in Tamsi and Jainath mandals of Adilabad district in Andhra Pradesh. The results of the study indicated that dealers were the major source of information for farmers to purchase various Bt cotton seed brands. Brahmma and Mallika were the most popular brands among the farmers in the study area. Majority of the farmers purchased Bt cotton seeds from the district private dealers by paying in cash. The sample farmers ranked high-yielding character of brands as a major influencing factor for the purchase of Bt cotton seeds and majority of the sample farmers were highly satisfied with fiber quality and were highly dissatisfied with the germination of Bt cotton seeds. Majority of the farmers were not ready for brand switchover, and the irrigated farmers were more loyal to their brands than the rainfed farmers. Variables such as yield performance, resistance to pest and disease, seed germination, new varieties, and new technology were found to be an important reason for brand switching.